Infections with Plasmodium falciparum during pregnancy affect VAR2CSA DBL-5 domain-specific T cell cytokine responses. (December 2016) - Gbédandé, Komi; Cottrell, Gilles; Vianou, Bertin; Ibitokou, Samad; Fernando, Aurax; Troye-Blomberg, Marita; Salanti, Ali; Moutairou, Kabirou; Massougbodji, Achille; Ndam, Nicaise; Deloron, Philippe; Luty, Adrian; et al.
Abstract Background Current knowledge of human immunological responses to pregnancy-associated malaria-specificPlasmodium falciparum protein VAR2CSA concerns almost exclusively B cell-driven antibody-mediated activity. Knowledge of VAR2CSA-specific T cell-mediated activity is minimal by comparison, with only a single published report of a study investigating VAR2CSA-derived peptide-specific T cell responses. The study described here represents an attempt to redress this balance. Methods Within the framework of a cohort study of 1037 pregnant Beninese, sub-groups were selected on the basis of the documented presence/absence of infection withP. falciparum and conducted detailed immunological assessments both at inclusion into the study and at delivery. Peripheral blood mononuclear cells were isolated, stimulated in vitro, and VAR2CSA DBL-5 domain-specific, IFN-γ-secreting T-cell frequencies and cytokine responses were quantified using flow cytometric techniques. Multivariate analyses were used to determine primarily whether the T cell-mediated DBL5-specific activity measured was associated with infection byP. falciparum adjusted for gravidity, anaemia and other cofactors. Results Infections withP. falciparum detected at inclusion were associated with enhanced non-specific TNF responses, whilst diminished non-specific and DBL-5-specific IL-10 responses were associated with infections detected at delivery. Infections during pregnancy led to enhanced non-specific and DBL-5-specific IFN-γ responses detectable at delivery but to concomitantly lower DBL-5-specific CD8+ IFN-γ responses. Prospective assessments indicated that non-specific pro-inflammatory responses detectable at inclusion in the study were associated with the occurrence of infections subsequently during pregnancy. Conclusions The findings represent a first step in elucidating the quantity and quality of cellular immunological responses to VAR2CSA, which will help in the development of the primary vaccine candidate for prevention of pregnancy-associated malaria.